Reducing the Fatality Rate of COVID-19 by Applying Clinical Insights From Immuno-Oncology and Lung Transplantation - Uckun, Fatih M. (Frontiers in Pharmacology, 2020)
There is an urgent need to identify effective strategies that can stop or reverse the inflammatory process that causes acute lung injury, ARDS, and multi-organ failure in COVID-19. Adaptive clinical trials with parallel enrollment to different arms each evaluating a rationally designed combination modality could provide the foundation for the accelerated identification of effective and safe multi-modality treatment algorithms for COVID-19 pneumonia. This article summarizes the insights and lessons learned from clinical immune-oncology trials as well as lung transplantation that are informing the clinical development of promising new strategies aimed at reducing the fatality rate in COVID-19.